Relationship between anterior or posterior femoral head necrosis and collapse based on MRI-defined key necrotic layer sets - Yawei Dong; Yan Yan; Jun Zhou; Kaiqiang Tang; Xiaohan Wang; Rui Quan; Jiaming Lin; Yan Jia; Zelu Zheng; Baohong Mi; Weiheng Chen (Journal of Orthopaedic Surgery and Research)
Abstract Background Current clinical studies on femoral head necrotic lesions primarily focus on the medial and lateral regions, while detailed MRI-based methods to evaluate the relationship between anterior or posterior necrosis and collapse remain lacking. Objective By defining the anterior and posterior positions of the femoral head in MRI, a method was proposed for rapid clinical prognosis assessment of femoral head necrosis based on necrotic location. Metohd A retrospective analysis was conducted on TSE sequence T1W1 coronal plane images from 200 cases of femoral head necrosis. The frequency of necrotic lesions appearing on each MRI layer was statistically analyzed to construct a high-frequency necrotic layer set. Among these cases, 100 hips were randomly selected, and the relationship between femoral head collapse at one-year follow-up and different high-frequency necrotic layer sets was analyzed to identify the key necrotic layer set. Based on this, the anterior and posterior regions of the femoral head were defined on MRI. The remaining 100 hips were used as a validation set to assess the impact of anterior or posterior necrosis of the femoral head, as defined by this method, on collapse. Results In this study, a total of eight high-frequency necrotic lesion layer sets (S1-S8) were constructed based on MRI data. Among them, S3 (L1 + L2 + L0 + L3) showed the strongest correlation with femoral head collapse, with an AUC of 0.662. Therefore, S3 was defined as the anterior side of the femoral head. Analysis of the validation set revealed that, using this method, the probability of femoral head collapse was 11.4 times higher when necrotic lesions appeared on the anterior side compared to the absence of necrosis on the anterior side. Conclusion In MRI, the anterior side of the femoral head corresponds to the S3 region, where necrosis increases the risk of collapse by 11.4 times.